The inherited disorders of haemoglobin: an increasingly neglected global health burden - Weatherall, David (Medknow Publications & Media Pvt Ltd, 2011)
An estimated 300,000 babies are born each year with a severe inherited disease of haemoglobin and that over 80 per cent of these births occur in low- or middle-income countries. As these countries go through the epidemiological transition, characterized by a reduction in childhood and infant mortality due to improved public health measures, infants who had previously died of these conditions before they were recognised are now surviving to present for diagnosis and treatment. For a variety of reasons, even in the rich countries there are limited data about the true frequency, natural history, and survival of patients with these disorders, information that is absolutely critical towards providing governments and international health agencies with accurate information about the true global health burden of these conditions. The situation can only be improved by major action on the part of the rich countries together with the formation of partnerships between rich and poor countries and input from the major international health agencies and funding organisations.